Product Development and Positioning Strategies for Seaclues Local Coffee - S Sarwita Salini; Virgo Simamora (Jurnal Indonesia Sosial Teknologi, 2024)
Seacules Coffee Shop uses psychographic, demographic, and behavioral factors to segment the market. Seaclues Coffee Shop's target market includes consumers between the ages of 18 and 45 who lead an active lifestyle and work as professionals or students. Seaclues Coffee Shop's goods are presented as premium coffee beverages. Seaclues serves high-quality coffee beans that have been roasted by a roaster. Coffee is served to customers with high quality services provided in a comfortable atmosphere. By implementing the right positioning strategy, Seaclues Coffee Shop can attract and retain the right customers, increase customer satisfaction, and build long-term loyalty. To respond to the dynamic market, Seaclues Coffee Shop has carried out product development by creating unique and high quality product variants. The quality of Seaclues coffee products comes from high quality coffee beans that go through a roasting process before being processed for serving. Seaclues Coffee Shop develops innovative and unique coffee products by utilizing spices. Accurate positioning and product development help Seaclues Coffee Shop create quality products that are different from competitors, which strengthens Seaclues Coffee Shop's presence in a competitive market.